2018
DOI: 10.3390/su10103621
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Social Lead-Up to a Human-Induced Disaster: The Gas Extraction-Earthquake Nexus in Groningen, The Netherlands

Abstract: The overwhelming impact that disasters have on societies is fed by socio-economic vulnerabilities and political-institutional factors. Disasters are, therefore, increasingly regarded as partially created by humans instead of as purely natural events. Although the “social creation” of disasters is assumed to occur “above the ground” and triggered by extreme natural events, this article explores several dimensions to the social creation of disasters, including technological and institutional dimensions from both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…A higher level of "earthquake experience" was correlated with decreased credibility for nearly all sources (see Table 4; Table 5). This broadly follows the findings shown in Bakema et al's work [30], who found that people who were adversely affected by a hazard showed greater distrust in government officials for not taking steps to mitigate the hazard. As in Bakema et al's study of induced seismicity in the Netherlands, the hazard in our case study has a human origin, yet only minimal steps have been taken to prevent the earthquakes or mitigate the risks they posed, and thus people may be resentful of the lack of action.…”
Section: The Effects Of Earthquake Experience On Source Credibilitysupporting
confidence: 88%
See 2 more Smart Citations
“…A higher level of "earthquake experience" was correlated with decreased credibility for nearly all sources (see Table 4; Table 5). This broadly follows the findings shown in Bakema et al's work [30], who found that people who were adversely affected by a hazard showed greater distrust in government officials for not taking steps to mitigate the hazard. As in Bakema et al's study of induced seismicity in the Netherlands, the hazard in our case study has a human origin, yet only minimal steps have been taken to prevent the earthquakes or mitigate the risks they posed, and thus people may be resentful of the lack of action.…”
Section: The Effects Of Earthquake Experience On Source Credibilitysupporting
confidence: 88%
“…Thus, when technological hazards occur, individuals often develop decreased trust in the government and other authorities deemed responsible. In the Netherlands, for example, incidents of significant induced seismicity have resulted in declining levels of trust in government authorities, in part because of a lack of visible mitigation efforts and a lack of transparency in the response to the hazards [30]. Conversely, in the United States, research has shown that if individuals view governmental agencies as knowledgeable and responsible parties regarding induced seismicity, they hold greater levels of trust in said agencies [65].…”
Section: Exposure To Induced Seismicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, corporate headquarters define the skylines of major cities and, in developed economies, they have replaced religion by becoming the new cathedrals and sites of worship [18]. Despite the enabling political support, policies and infrastructural support for the burgeoning private sector, many national and regional governments and their institutions are straining under crushing debt burdens, lack of revenue streams, mounting civic responsibilities, and growing public discontent and distrust in government [19][20][21][22][23]. While the needs of society were traditionally part of the remit of the state, increasing corporate power challenges and undermines this custodianship [18][19][24][25][26][27][28][29].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For example, in Canada, whose economy focuses significantly on carbon extraction, the Athabasca, Cold Lake and Peace River bitumen extraction projects comprise vast industrial wastelands visible from space, raising concerns about the so-called Dutch disease, indicating that boom industries can often have a range of negative side effects in other parts of the economy (Carroll, 2017). Another example is the earthquakes provoked, since 1998, in Groningen, Holland, by industrial gas extraction (Bakema et al , 2018). In the Scandinavian countries, extractivism in terms of mining and vast timber production has also played a significant role (Sjöstedt Landén and Fotaki, 2018).…”
mentioning
confidence: 99%